The Historical Trace of Francis Bacon’s Concept of “Knowledge Is Power” and Its Relevance to the Development of Social Sciences - Aulia Rahmi Putri; Siti Fatimah; Syafri Anwar; Ahmad Nurhuda (Tarikhuna: Journal of History and History Education, 2025)
This article examines the historical traces and epistemological relevance of Francis Bacon’s foundational concept, “knowledge is power”, to the development of Social Sciences. This study adresses need to understand the philosophical roots of modern social inquiry and its implications for contemporary educational practice. This research uses a qualitative approach with a historical and philosophical literature study method. The data sources consist of Francis Bacon's major works, including The Advancement of Learning, Novum Organum, and The New Atlantis. Data analysis was utilized using content analysis techniques with stages of data reduction, concept grouping, and theoretical synthesis. The results demonstrate that Bacon’s thought about knowledge established a critical framework emphasizing empiricism, inductive reasoning, and the systematic deconstruction of cognitive biases. which significantly contributed to the formation of social studies methodology through the use of empirical data and a problem-solving orientation. Ultimately, these findings confirm that Bacon’s epistemology remains highly relevant in the 21st century, particularly in fostering inquiry-based learning, problem-based learning, and critical literacy to develop students who are analytical, reflective, and capable of navigating complex social dynamics.